HLA-DQB1*05:02 Allele Association with Anti-Tuberculosis Drug Induced Liver Injury: A Single-Hospital Based Study in Jakarta, Indonesia - Kinasih Prayuni; Hilyatuz Zahroh; Syafrizal Syafrizal; Rika Yuliwulandari (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2023)
Past studies have delved into the genetic factors underlying anti-tuberculosis drug-induced liver injury (AT-DILI), primarily concentrating on polymorphisms in genes responsible for drug-metabolizing enzymes. However, the immune system's potential impact on drug adverse effects, specifically through genes such as HLA, has received limited attention. Previous research has notably revealed an association between HLA-DQB1*05 and AT-DILI, specifically the prevalence of the HLA-DQB*05:02 allele in AT-DILI patients. In light of this, our study aimed to investigate a potential link between HLA-DQB1*05:02 alleles and AT-DILI. In this study, we included 51 AT-DILI cases and 59 controls belonging to the Javanese ethnic group. The HLA-DQB1*05:02 genotypes were determined using a customized PCR-based typing method, and the results were further confirmed by analyzing five samples via the Luminex assay. Our findings revealed a significant association between HLA-DQA1*05: 02 and the risk of AT-DILI (P = 0.022; OR (95% CI) = 6.11 (1.25-29.74)). Moreover, the consistent results obtained from the Luminex assay validated the reliability of the custom PCR-based genotyping approach. This preliminary study sheds light on the relationship between the HLA-DQB1*05:02 allele and AT-DILI within the Indonesian population. Furthermore, our study demonstrates the dependability of custom PCR-based genotyping in detecting HLA-DQB1*05:02 alleles. Nevertheless, further research is imperative to corroborate and expand upon our findings.